2007
DOI: 10.1007/s00464-006-9076-9
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Endoscopic Extraperitoneal Herniorrhaphy: Where Do We Stand in 2005?

Abstract: Inguinal hernia repair is a common surgical procedure, but the most effective surgical technique remains controversial. The evolution of laparoscopic techniques has allowed reproduction of open preperitoneal repair via an endoscopic total extraperitoneal (TEP) approach. More recently, the advent of comprehensive training in laparoscopy has allowed TEP to continue evolving as the feasibility of this approach gains recognition as a preferable technique. Once considered very difficult to learn, TEP currently is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 50 publications
(25 reference statements)
0
29
0
Order By: Relevance
“…However, now, with a decade of experience in laparoscopic hernia repair, the cost of TEP repair is comparable with that of open repair [24,25], mainly due to successful cost-reduction strategies (factors related to learning curve effects, including reduced operative time, surgical errors, unnecessary instrumentations, and materials, plus global variables including complications, postoperative pain, recurrences, and return to work).…”
Section: Discussionmentioning
confidence: 99%
“…However, now, with a decade of experience in laparoscopic hernia repair, the cost of TEP repair is comparable with that of open repair [24,25], mainly due to successful cost-reduction strategies (factors related to learning curve effects, including reduced operative time, surgical errors, unnecessary instrumentations, and materials, plus global variables including complications, postoperative pain, recurrences, and return to work).…”
Section: Discussionmentioning
confidence: 99%
“…There was no infection or recurrence with either type of mesh. Conclusion Lightweight PP mesh is associated with significantly better outcomes in TEP inguinal herniorrhaphy as compared with heavyweight PP mesh.Keywords TEP Á Mesh Á Lightweight mesh Á Groin pain Á Postherniorrhaphy pain Á Sexual dysfunction Á Ejaculatory pain Á Mesh inguinodynia Totally extraperitoneal repair (TEP) has become a standard-of-care procedure for inguinal hernias [1]. Polypropylene and the other mesh materials used in hernia surgery help in strengthening the weakened native tissue.…”
mentioning
confidence: 99%
“…Surgical dissection, mesh fixation, and mesh-induced entrapment have been cited as the potential causes of groin pain. 25 Several studies have shown that minimally invasive hernia repair (TEP, TAPP) are associated with significantly less early and chronic pain as compared with open hernia repair. 26,27 In present study, the incidence of chronic groin pain was less in 3D mesh.…”
Section: Discussionmentioning
confidence: 99%